Graphene in chitin based passive Q-switcher - Zuikafly, Siti Nur Fatin; Wan Nawawi, Wan Mohd Fazli; Ngee, Lim Hong; Yahaya, Hafizal; Yahya, W. J.; Ahmad, Faizah (IOP Publishing, 2019)
Many materials have been utilized as saturable absorbers in generating pulsed lasers. By incorporating them with host polymers such as polymethylmethacrylate (PMMA), polyvinyl alcohol (PVA) and polyethylene oxide (PEO), the process of saturable absorber integration into the laser cavity is made easier. This work reported the generation of Q-switched pulsed lasers based on graphene embedded in chitin saturable absorber. Graphene: chitin with a concentration of 1:1 and 1.5:1 are integrated into a fiber laser cavity and the laser performance of both SAs are recorded and compared. The graphene chitin SA of 1:1 concentration produces a higher repetition rate and shorter pulse duration of 111.77 kHz and 1.328 μs, respectively. However, the SA with higher graphene content operated at a larger range of input pump power yielding a higher instantaneous peak power and pulse energy of 7.29 mW, and 14.37 nJ, respectively. This work introduces chitin as a potentially excellent natural host polymer as an alternative to conventional ones such as polyvinyl alcohol (PVA) and polyethylene oxide (PEO).